Psicomotricidad para la orientación y movilidad de los niños y niñas escolares residentes ciegos del instituto fiscal especial para ciegos Byron Eguiguren Club de Leones” en la ciudad de Loja periodo lectivo 2018 - Vivanco Arciniegas, Michelle Katherine (2018)
The present thesis entitled: Psychomotor skills for the orientation and mobility of schoolchildren blind residents of the Special Prosecutor Institute for the Blind Byron Eguiguren "Club de Leones" in the city of Loja 2018 academic year, whose general objective is: Contribute to the development of The psychomotricity for independent displacement was developed with the purpose of determining the main causes that impede a complete independent displacement, for which instruments such as the psychomotor skill assessment scale adapted for children with blindness from Huiracocha, Piedra and Palomeque were used; Cuenca-2004, the Adapted Orientation and Mobility Scale in the Pre-Bastón and Bastón stage of Ruth Hidalgo, Cuenca-2011 applied to a sample of 6 resident schoolchildren with total blindness followed by an interview with 5 officials of the institute, thereby tending to systematize through a plan of specific activities that help improve their psychomotricity and autonomy to blind resident schoolchildren. In the process, the scientific, descriptive, analytical, synthetic and inductive methods were used, which were finalized after the interviewing technique to the officials, finalizing with the conclusions and recommendations that allow to optimize the basic needs giving rise to the proposal of the plan of activities to improve psychomotor skills related to the orientation and mobility of blind resident schoolchildren